Analysis of hospital cost outcome of DHA-rich fish-oil supplementation in pregnancy: Evidence from a randomized controlled trial. (December 2015) - Ahmed, Sharmina; Makrides, Maria; Sim, Nicholas; McPhee, Andy; Quinlivan, Julie; Gibson, Robert; Umberger, Wendy
Abstract: Objective: Recent research emphasized the nutritional benefits of omega-3 long chain polyunsaturated fatty acids (LCPUFAs) during pregnancy. Based on a double-blind randomised controlled trial named "DHA to Optimize Mother and Infant Outcome" (DOMInO), we examined how omega 3 DHA supplementation during pregnancy may affect pregnancy related in-patient hospital costs. Method: We conducted an econometric analysis based on ordinary least square and quantile regressions with bootstrapped standard errors. Using these approaches, we also examined whether smoking, drinking, maternal age and BMI could influence the effect of DHA supplementation during pregnancy on hospital costs. Results: Our regressions showed that in-patient hospital costs could decrease by AUD92 ( P <0.05) on average per singleton pregnancy when DHA supplements were consumed during pregnancy. Our regression results also showed that the cost savings to the Australian public hospital system could be between AUD15 – AUD51 million / year. Conclusion: Given that a simple intervention like DHA-rich fish-oil supplementation could generate savings to the public, it may be worthwhile from a policy perspective to encourage DHA supplementation among pregnant women.